In vitro screening for the anti-anaphylactic agent in thonningia sanguinea - Nyarko, A.K.; Addy, M.E. (Journal of Ethnopharmacology, 1994)
Thonningia sanguinea, used prophylactically against bronchial asthma, is anti-anaphylactic and anti-asthmatic in guinea pigs when given orally. The aqueous extract of the plant and its fractions were screened in vitro for their effects on anaphylactic- and histamine-induced contractions, and the results compared with those obtained in vivo when the whole extract was administered orally. The comparison showed similar anti-anaphylactic properties of the plant material in the two systems of administration, but the effects on histamine-induced contractions differed from the in vivo ones, suggesting that the anaphylactic assay system should be preferred for the screening in vitro. The anti-anaphylactic substance(s) extracted into n-butanol. The active portions of the extracted components appeared to be stable to acid digestion. Thin layer chromatographic analysis of the butanol extract and preliminary chemical analysis suggest that these substances are polyhydroxy/phenolic in nature